PENGARUH MODEL PEMBELAJARAN ARIAS DENGAN PROBLEM BASED LEARNING TERHADAP MOTIVASI DAN HASIL BELAJAR IPA SISWA KELAS IV SDN LIWUNG KABUPATEN LOMBOK TENGAH - Laili Alfi Rahmatin (JURNAL ILMIAH GLOBAL EDUCATION, 2021)
This study aims to determine the differences in learning motivation and science learning achievement between students who follow the ARIAS learning model with Problem Based Learning and conventional learning. A total of 58 fourth grade students at SDN Liwung were selected as samples . The study used experiment research design with the non-equivalent post-test only control group design. The data of motivation learning collected by questioner and learning achievement collected by objective test. Validity test of questioner and test analyzed by used Product Moment and Point Biserial. The reliability test of questioner and the test used by Alpha Cronbach and KR-20. The hypothesis test used ANAVA and MANOVA. The result showed us that : first, there was a significant difference between the students that treated with ARIAS learning model with Setting Group Investigation than those who treated with conventional learning model (F=10,373 and Sig.=0,020; p<0,05).